PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN METODE PROBLEM SOLVING PADA SISWA KELAS V SEKOLAH DASAR - Sari, Weli Sartika (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The students’ result in 5th grade of elementary school 03 IV Koto Aur Malintang are still low. The cause is the teacher has not used a good method yet in teaching. This thesis is to describe the improvement of students’ result in learning civics through problem solving method at 5 grader SDN 03 IV Koto Aur Malintang. The students’ got 70 and after using this method increase become 78.3.   Kata kunci : hasil belajar, metode problem solving, siswa sd